(untitled) (ItalianoLinguadue, 2012)
L’articolo propone un progetto didattico per l’insegnamento dell’italiano L2 nella scuola superiore di primo grado che prevede l’inserimento di studenti stranieri, provenienti da paesi diversi, in un gioco di ruolo didattico ispirato alla saga di Harry Potter.Particolare attenzione è data al laboratorio Hogwarts, un laboratorio specifico il cui obiettivo è quello di promuovere l’interazione, la socializzazione, ma soprattutto l’apprendimento dell’italiano come lingua di comunicazione. La didattica del laboratorio fonde insieme elementi del metodo comunicativo ed elementi del metodo audiolinguale richiamando la didattica ludica in quanto il gioco è assunto come modalità strategica di apprendimento. L’idea che sta alla base del laboratorio Hogwarts è quella di coinvolgere gli apprendenti, stimolarne l’interesse e la curiosità attraverso l’utilizzo di materiale video (visual stimuli) e attraverso l’attività ludica che mantiene viva la loro attenzione e la loro motivazione favorendone l’apprendimento linguistico attraverso il divertimento. TEACHING ITALIAN L2 IN MIDDLE SCHOOL. THE HOGWARTS LAB: LEARNNG BY PLAYING The article illustrates a project aimed at teaching Italian as a second language. The target audience is middle school students from different countries and with different L1 backgrounds. Students take part in didactic role-plays inspired by the Harry Potter series. Special emphasis is given to the Hogwarts Language Lab, which aims to promote interaction, socialization and second language acquisition. The Lab teaching strategy combines elements of the communicative approach and the audio-lingual method with role-playing. The principle behind the Hogwarts Lab is that the students have to be active participants rather than passive observers. Their involvement can be increased and their interest can be raised through the use of the video input (visual stimuli) and role-playing as a teaching strategy. Students are encouraged to carry out tasks and activities using cooperation and collaboration, using Italian to communicate. They take an active part and there is increased involvement as the students “learn while they are playing”.